Comparison of non‐reflective boundary conditions for a free‐rising turbulent axisymmetric plume. (19th March 2013) - Hattori, T.; Norris, S.E.; Kirkpatrick, M.P.; Armfield, S.W.
SUMMARY The stability and accuracy of radiation type non‐reflective outflow boundary conditions, as well as the standard Neumann boundary condition with zero normal derivative, have been compared for the numerical simulation of a turbulent axisymmetric plume with Reynolds number of 7700 and Prandtl number of 0.71. Comparison of the performance of the boundary conditions with respect to each other, and to the results obtained for an extended domain, shows that a one‐dimensional scheme in which advection and diffusion terms are included in the radiation equation is the optimum approach for the plume simulation. Copyright © 2013 John Wiley & Sons, Ltd.